Phytoconstituents from Sidastrum micranthum (A. St.-Hil.) Fryxell (Malvaceae) and antimicrobial activity of pheophytin a - Roosevelt Albuquerque Gomes; Yanna Carolina Ferreira Teles; Fillipe de Oliveira Pereira; Luis Alberto de Sousa Rodrigues; Edeltrudes de Oliveira Lima; Maria de Fátima Agra; Maria de Fátima Vanderlei de Souza (Universidade de São Paulo, 2015)
abstract Sidastrum micranthum (A. St.-Hil.) Fryxell, a member of the Malvaceae family, is called malva preta in Brazil. As this species is commonly used to treat bronchitis, cough, and asthma, better knowledge of its chemical compounds is important. The phytochemical study of its hexane extract, using chromatographic techniques, led to isolation of six compounds: the triterpene isoarborinol, a mixture of sitosterol and stigmasterol, sitosterol-3-O-β-D-glucopyranoside, pheophytin a, and 132-hydroxy-(132-S)-pheophytin a. Structural identification of these compounds was carried out using spectroscopic methods such as IR and 1D and 2D NMR (HOMOCOSY, HMQC, HMBC, and NOESY). Compounds isolated from S. micranthum were screened for their in vitro antifungal and antibacterial activity against twenty fungal and bacterial standard strains. Pheophytin a exhibited antimicrobial action against all microorganisms tested.